Comprehensive review: Frailty in pancreas transplant candidates and recipients. Issue 2 (13th January 2023) - Parsons, Ronald F.; Tantisattamo, Ekamol; Cheungpasitporn, Wisit; Basu, Arpita; Lu, Yee; Lentine, Krista L.; Woodside, Kenneth J.; Singh, Neeraj; Scalea, Joseph; Alhamad, Tarek; Dunn, Ty B.; Rivera, Franco H. Cabeza; et al.
Abstract: Well‐selected patients with kidney disease and diabetes mellitus who undergo simultaneous kidney‐pancreas transplantation often experience dramatic improvements in quality of life and long‐term survival compared to those who remain on medical therapy. Over the past several years the importance of frailty in the pancreas transplant candidate and recipient populations has grown. More patients with advanced age have entered the waitlist, and complications from prolonged diabetes, even in younger patients, have created increased evidence of risk for frailty. Given these concerns, and the broad challenges facing pancreas transplantation volumes overall, we generated this review to help establish the impact and implications. We summarize the interplay of immunological factors, aging, environmental factors, diabetes mellitus, and chronic kidney disease that put these patients at risk for frailty. We discuss its measurement and recommend a combination of two instruments (both well‐validated and one entirely objective). We describe the outcomes for patients before and after pancreas transplantation who may have frailty, and what interventions can be taken to mitigate its effects. Broader investigation into frailty in the pancreas transplant population is needed to better understand how to select patients for pancreas transplantation and to how manage its consequences thereafter.